PP62 Study of the Bioactive Compounds of Apis mellifera honey obtained from Eugenia stipitata (Arazá). - Cuellar Alvarez, Liceth Natalia; Herrera, Yina; Valencia, Mayrin O.; Maldonado, Jhon Ironzi; García Rios , Alejandro (Revista Productos Naturales, 2025)
In the present study, five types of honey were evaluated: two containing Arazá floral nectar (Arazá honey) (M001, M002) collected in the department of Caquetá, and three others from southern Colombia. The characteristics of these honeys were evaluated by examining their physicochemical properties, color, and their constituent compounds, which were confirmed by GC-MS analysis. Fifteen phenolic compounds were detected in honey sample M002, the most abundant phenolic compounds tentatively detected were 3,4-dihydroxybenzoic acid, salicylic acid, caffeic acid, chlorogenic acid, pcumaric acid, ferulic acid, gallic acid, syringic acid, isorhamnetin, kaempferol, luteolin, naringenin, pinobanksin, quercetin and rutin